Management of depression during the perinatal period: state of the evidence - Idan Falek; Mary Acri; Joanna Dominguez; Jennifer Havens; Mary McCord; Sarah Sisco; Wendy Wilcox; Kimberly Hoagwood (International Journal of Mental Health Systems, 2022)
Abstract Background Perinatal depression (PND) is a prevalent ailment that affects both the woman and her family. Addressing PND in primary health care, such as pediatrics and obstetric care settings, has been proposed as an effective way to identify and treat women. Objective The purpose of this study is to examine best practices for management of PND in obstetric and pediatric settings, as well as investigate the evidence that supports the guidelines. Methods Guidelines were identified through a literature search and discussion with experts in the field of perinatal depression, while evidence was examined through a literature search of reviews and thereafter experimental studies. Results Twenty-five guidelines, across 17 organizations were retained for analysis. Findings suggest that there is little or varied guidance on the management of PND, as well as a lack of specificity. Treatment was the topic most frequently reported, followed by screening. However best practices vary greatly and often contradict one another. Across all areas, there is inadequate or contrasting evidence to support these guidelines. Conclusions Although there was consensus on the key steps in the pathway to care, the review revealed lack of consensus across guidelines on specific issues relating to identification and management of depression during the perinatal period. Clinicians may use these recommendations to guide their practice, but they should be aware of the limitations of the evidence supporting these guidelines and remain alert to new evidence. There is a clear need for researchers and policymakers to prioritize this area in order to develop evidence-based guidelines for managing perinatal depression.